Uinta Fremont rock art in southwestern Wyoming: Marking the Fremont northern periphery. (3rd April 2017) - Keyser, James D.; Poetschat, George
Abstract : The Fremont Culture, identified throughout eastern Utah and northwestern Colorado, is best known for Classic Vernal Style anthropomorphs. These figures show large trapezoidal bodies decorated with necklaces and crowned with elaborate horned headgear usually embellished with earrings or hairbobs. Recent research has identified Classic Vernal Style and other Fremont anthropomorphs at seven southwestern Wyoming sites extending from the Utah/Wyoming border to Rock Springs, more than 60 km north. This Fremont rock art indicates the presence of actual groups with a Fremont world view who were marking the northern periphery of their territory with a fully developed version of their ritual rock art complex.